Environment: The third teacher - Merewether, Jane (Oxford University Press, 2017)
We value space because of its power to organize and promote pleasant relationships between people of different ages, create a handsome environment, provide changes, promote choices and activity, and its potential foe sparking all kinds of social, affective, and cognitive learning. All of this contributes to a sense of well-being and security in children. We also think that the space has to be a sort of aquarium that mirrors the ideas, values, attitudes, and cultures of the people who live within it. (Malaguzzi cited in Gandini, 2012a, p.339)